Ionospheric Response at Conjugate Locations During the 7–8 September 2017 Geomagnetic Storm Over the Europe‐African Longitude Sector. Issue 10 (6th October 2020) - Habarulema, John Bosco; Katamzi‐Joseph, Zama T.; Burešová, Dalia; Nndanganeni, Rendani; Matamba, Tshimangadzo; Tshisaphungo, Mpho; Buchert, Stephan; Kosch, Michael; Lotz, Stefan; Cilliers, Pierre; Mahrous, Ayman
Abstract: This paper focuses on unique aspects of the ionospheric response at conjugate locations over Europe and South Africa during the 7–8 September 2017 geomagnetic storm including the role of the bottomside and topside ionosphere and plasmasphere in influencing electron density changes. Analysis of total electron content (TEC) on 7 September 2017 shows that for a pair of geomagnetically conjugate locations, positive storm effect was observed reaching about 65% when benchmarked on the monthly median TEC variability in the Northern Hemisphere, while the Southern Hemisphere remained within the quiet time variability threshold of ±40%. Over the investigated locations, the Southern Hemisphere midlatitudes showed positive TEC deviations that were in most cases twice the comparative response level in the Northern Hemisphere on the 8 September 2017. During the storm main phase on 8 September 2017, we have obtained an interesting result of ionosonde maximum electron density of the F2 layer and TEC derived from Global Navigation Satellite System (GNSS) observations showing different ionospheric responses over the same midlatitude location in the Northern Hemisphere. In situ electron density measurements from SWARM satellite aided by bottomside ionosonde‐derived TEC up to the maximum height of the F2 layer (hmF2) revealed that the bottomside and topside ionosphere as well as plasmasphere electron content contributions to overall GNSS‐derived TEC were different in both hemispheres especially for 8 September 2017 during the storm main phase. The differences in hemispheric response at conjugate locations and on a regional scale have been explained in terms of seasonal influence on the background electron density coupled with the presence of large‐scale traveling ionospheric disturbances and low‐latitude‐associated processes. The major highlight of this study is the simultaneous confirmation of most of the previously observed features and their underlying physical mechanisms during geomagnetic storms through a multi–data set examination of hemispheric differences. Key Points: The storm led to TEC increase which was at least twice in Southern Hemisphere than Northern Hemisphere midlatitudes on 8 September 2017 Processes of low‐latitude origin, thermospheric composition changes, and TIDs contributed to the observed positive ionospheric storm effects Ionospheric bottomside and topside/plasmasphere contributions to TEC were different in both hemispheres during the storm main phase